Reveal: new ecologies for an urban stream system - McDowell, Charles (Kansas State University, 2011)
Throughout the history of Kansas City, the Brush Creek Corridor has experienced severe flooding which, on numerous occasions, has resulted in loss of life. This urban stream supports a high profile area of the city. It is located adjacent to what is considered Kansas City’s most elite shopping district, the JC Nichols Country Club Plaza, the University of Missouri - Kansas City urban campus, as well as numerous high density residential units. The stream corridor has been confined due to the encroachment of the surrounding urban environment which has minimized many opportunities for the future management of Brush Creek. There have been many flood control projects but these solutions have not been effective in reducing along the entire corridor. Previous projects have been done in a way that alienates urban dwellers from Brush Creek and does not allow pedestrians to utilize the stream corridor as an effective urban green space. The Brush Creek Corridor can be redesigned to revitalize the existing area by embracing natural ecological processes in order to create a more sustainable urban stream system. Brush Creek can be envisioned in a way that will enhance visitor experience by exposing and revealing the ecological processes to the users without inhibiting the functionality of those natural processes. Four project goals have been identified through research: improve, connect, and educate. In order to achieve the project goals, a set of sites are to be selected from the corridor. A corridor study is done to identify sites by assessing factors related to the site’s ability to improve, connect, and educate. Once the sites have been identified and defined, programming and site design strategies will be implemented to relate to the project goals. The selected sites within the Brush Creek Corridor will be models for experience oriented urban stream design. The project area will harbor healthy ecosystems with integrated pedestrian oriented spaces that connect the corridor, improve environmental conditions, and support environmental education. These projects will be catalysts for experience oriented ecological design solutions throughout the Brush Creek Corridor in the future.
Keywords: Ecological design; Brush Creek; Stream corridor; Landscape Architecture (0390)